Cooperative Decay of N Atoms in a Ring Configuration - Nicola Piovella (Atoms)
We provide an analytic expression of the spectrum of the cooperative decay rate of N two-level atoms regularly distributed on a ring in the single-excitation configuration. The results are obtained first for the scalar model and then extended to the vectorial light model, assuming all the dipoles are aligned.